Analysis of related risk factors of lung metastasis after laparoscopic radical hysterectomy of cervical cancer. Issue 18 (7th May 2021) - Henglian, Liu; Jiajun, Wang; Caixia, Wang; Gang, Lu; Min, Xia
Abstract : Abstract: To explore the risk factors of lung metastasis in patients after laparoscopic radical hysterectomy (LRH) of cervical cancer (CC). The clinical data of CC patients with clinical stage of IA1 –IIA2 diagnosed in our hospital from April 2007 to October 2015 were collected. According to the situation of metastasis, the patients were divided into lung metastasis (n = 73) and non-lung metastasis group (n = 2076). The clinical data were compared between 2 groups, and logistic stepwise regression model was used to analyze the risk factors of lung metastasis in patients with CC after LRH. The incidence of lung metastasis after LRH of CC was 3.39%, and 67.13% of patients with lung metastases had no obvious clinical symptoms. 15.06% patients had lung metastasis in the first year, 38.35% in the second year, 43.83% in the third year and later. The postoperative lung metastasis of CC was related to tumor diameter ( P < .001), pathological type ( P < .001), interstitial invasion depth ( P < .001), pelvic lymph node metastasis (PLNM, P < .001), vascular tumor thrombus ( P = .011), tumor uterine invasion ( P = .002), and abnormal preoperative tumor markers ( P = .015). However, it was not related to age, clinical stage, tumor growth pattern, tumor differentiation, and para-aortic lymph node metastasis ( P > .05). Logistic regression analysis revealed non-squamous cell carcinoma ( P = .022), tumor diameter ≥4 cm ( P = .008), interstitial invasion depth >2/3 ( P = .003), PLNM ( P = .007), and tumor uterine invasion ( P = .037) is an independent risk factor for lung metastasis after LRH of CC. Non-squamous cell carcinoma, tumor diameter ≥4 cm, tumor interstitial invasion depth >2/3, PLNM, and tumor uterine invasion are independent risk factors for lung metastasis after LRH of CC.